Inteligencja emocjonalna młodych mężczyzn o wyższym i niższym poziomie dojrzałości psychicznej do małżeństwa - Dakowicz, Andrzej (Civitas et Lex, 2024)
The aim of the paper was to determine whether the mental maturity for marriage of young men is related to emotional intelligence? In this article, mental maturity for marriage is understood as the sum of three significant elements that build long-term interpersonal relationships: 1) self acceptance; 2) internal integration; 3) approach to marriage and family life. During research there took a part 90 men. The obtained results showed that young men with a higher level of psychological maturity for marriage are characterized by much greater emotional intelligence than men with a lower level of psychological maturity for marriage. This is manifested, among other things, in better abilities to use experienced emotions when solving problems encountered in life.